Screening Diverse Weedy Rice (Oryza sativa ssp.) Mini Germplasm for Tolerance to Heat and Complete Submergence Stress During Seedling Stage - Stallworth, Shandrea; Shrestha, Swati; Schumaker, Brooklyn; Roma-Burgos, Nilda; Tseng, Te-Ming (Frontiers in Agronomy, 2021)
Rice is a staple food for more than 3.5 billion people worldwide, with Asia producing almost 90% of the global rice yield. In the US, rice is primarily produced in four regions: Arkansas Grand Prairie, Mississippi Delta, Gulf Coast, and California. As global temperatures continue to rise and fluctuate, crop-breeding programs must continue to evolve. Unfortunately, sudden submergence due to climate change and unpredictable flash flooding can cause yield reduction up to 100% and affect 20 million ha of agricultural farmlands. Similarly, it has been demonstrated that temperatures higher than 34°C can cause spikelet infertility resulting in up to 60% reduction in yield. One major drawback to developing abiotic stress-tolerant rice is the loss of critical traits such as vegetative vigor, fertility, and quality, which are essential in increasing rice’s economic return for farmers. To replace traits lost in past breeding endeavors, weedy rice (WR) has been proposed as a source for novel trait discovery to improve rice breeding programs. Therefore, the goal of this study was to screen and identify heat and submergence tolerant WR accessions. A WR mini germplasm was exposed to heat (38°C) and complete submergence for 21 days. After each treatment, height was recorded every 7 days for 28 days, and biomass was collected 28 days after treatment. The average height reduction across all accessions was 19 and 21% at 14 and 28 days after treatment (DAT) for the heat-stress treatment. The average height reduction across all accessions was 25 and 33% for the complete submergence stress. The average biomass reduction across all accessions was 18 and 21% for heat and complete submergence stress, respectively. Morphologically, at 28 DAT, 28% of the surviving WR accessions in the heat-stress treatment with less than 20% height reduction present straw-colored hull types with no awns present. When morphologically comparing WR accessions in the complete submergence-stress treatment, 33% of the WR accessions presented with black hull coloring and no awns, suggesting that these specific biotypes may play a role in the increased resilience of WR populations. Elite WR accessions that can survive the effects of climate change are highlighted.